O emprego de auxiliares de saúde em áreas de desenvolvimento: alguns conceitos - Tornero, Nilton (Semina: Ciências Exatas e Tecnológicas, 2004)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> In this paper the author discusses the real meaning of health auxiliary according to World Health Organization criteria. Next he discusses_ the relationship between health auxiliary and primary sanitary aid models, trying to show how the right comprehension of some elements of theses models will be of the highest importance to the definition of the auxiliary's functions. Among such elements he calls attention to the relationships between health services and other services offered to the community by other organizations: the choice of the workable area as pre-requisites to the training of personnel; relationships among the primary health aid and the services of campaign, the preventive and curative medicine and general guidelines for the pacification, management and training of health manpower.